Diverse sources of reward value signals in the basal ganglia nuclei transmitted to the lateral habenula in the monkey - Hong, Simon; Hikosaka, Okihide (Frontiers in Human Neuroscience, 2013)
The lateral habenula (LHb) plays an important role in motivational decision making. Neurons in the primate LHb signal negative ‘reward prediction errors’ and inhibit midbrain dopamine (DA) neurons. These negative reward prediction error signals in the LHb are, at least partly, provided by a distinct group of neurons in the border region of the globus pallidus internal segment (GPb). However, it is still unclear whether other basal ganglia nuclei provide the LHb with reward signals, either through the GPb or through different circuits. As a first step to answer this question, we electrically stimulated various parts of the basal ganglia and monitored the neural activity in the LHb in the awake monkey. First, we found that low intensity stimulations in the GPb and the internal segment of the globus pallidus (GPi) evoked a short latency (5 ms) excitatory response in LHb neurons. Second, LHb neurons were inhibited by stimulations in the ventral pallidum (VP). These results suggest that reward-related signals are transmitted to the LHb mainly through excitatory connections from the GPb and inhibitory connections from the VP. Finally, excitations or inhibitions are induced in LHb neurons from diverse but patchy regions in the striatum. These effects have considerably longer latencies, suggesting that they may be mediated by the GPb or the VP. The patchy nature of the stimulation effect raises the possibility that the striosomes are the source of reward-related signals transmitted to the LHb.